(untitled) (International Journal of Food and Nutritional Sciences, 2022)
While I have always been interested in business and entrepreneurship and research on them, this period has solidified my decision. I had been looking for opportunities to research more as research scholar at companies during my doctorate but due to the pandemic, these opportunities were very limited. However, what impressed me most was how the Indian corporate sector, including Indian companies of all sizes and multinationalcompanies in India, hasgoneoutofitsway to help thosehave lost their jobs or areexperiencingdifficultiesin their families.I realized that CSR is animportant aspect of business, especially in India, and I wanted to explore it further. My research paper is on CSR, type, scope, top 2 Indian companies in termsof CSR spend. It also has case studies of two large Indian companies that I admire for their diversity,ITC and TCS, Overall, I am impressed not only by the scale and diversity of CSR activities and budgets for Indian companies, but also by how they go beyond what is prescribed.